Differential Role of Pontomedullary Glutamatergic Neuronal Populations in Sleep-Wake Control - Erickson, Evelyn T. M.; Ferrari, Loris L.; Gompf, Heinrich S.; Anaclet, Christelle (Frontiers in Neuroscience, 2019)
Parafacial zone (PZ) GABAergic neurons play a major role in slow-wave-sleep (SWS), also called non-rapid eye movement (NREM) sleep. The PZ also contains glutamatergic neurons expressing the vesicular transporter for glutamate, isoform 2 (Vglut2). We hypothesized that PZ Vglut2-expressing (PZVglut2) neurons are also involved in sleep control, playing a synergistic role with PZ GABAergic neurons. To test this hypothesis, we specifically activated PZVglut2 neurons using the excitatory chemogenetic receptor hM3Dq. Anatomical inspection of the injection sites revealed hM3Dq transfection in PZ, parabrachial nucleus (PB), sublaterodorsal nucleus (SLD) or various combinations of these three brain areas. Consistent with the known wake- and REM sleep-promoting role of PB and SLD, respectively, chemogenetic activation of PBVglut2 or SLDVglut2 resulted in wake or REM sleep enhancement. Chemogenetic activation of PZVglut2 neurons did not affect sleep-wake phenotype during the mouse active period but increased wakefulness and REM sleep, similar to PBVglut2 and SLDVglut2 activation, during the rest period. To definitively confirm the role of PZVglut2 neurons, we used a specific marker for PZVglut2 neurons, Phox2B. Chemogenetic activation of PZPhox2B neurons did not affect sleep-wake phenotype, indicating that PZ glutamatergic neurons are not sufficient to affect sleep-wake cycle. These results indicate that PZ glutamatergic neurons are not involved in sleep-wake control.